Temperature and Humidity Monitoring in Dry Land of Cayene Pepper Based on Internet of Thing (IoT) - Ida Ayu Widhiantari; Joko Sumarsono; M Abul Auni Annawawi (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2023)
In general, plant growth will be disrupted if the environmental temperature is not suitable, even the plants will be damaged, which can cause a decrease in quality and quantity. Problems that often occur and are difficult to avoid include temperature and humidity conditions on agricultural land. Therefore it is necessary to do handling to be able to minimize the occurrence of damage that can occur in the land caused by environmental influences. This study aims to design a temperature and humidity monitoring system based on the Internet of Things (IoT). The research was carried out by designing electronic circuits from monitoring systems, hardware, software, and testing the systems that had been made. Technology supported by the use of DHT22 sensors can read temperature and humidity data in real time. Based on the research results, it was found that the DHT22 sensor used worked with the best accuracy on day 21 with an error percentage of 0% and the worst accuracy occurred on day 31 with an error percentage of 18.5%.  Keywords: Internet of thing,Humidity,DHT22 Sensor,Air temperature.